3D printing of Al2O3 photonic crystals for terahertz frequencies. Issue 3 (4th January 2016) - Tubío, Carmen R.; Nóvoa, José A.; Martín, Jorge; Guitián, Francisco; Salgueiro, José R.; Gil, Alvaro
Abstract : A simple 3D printing technique is used to fabricate three-dimensional photonic crystals made of Al2 O3 and intended to be functional for terahertz frequencies. The process is completed by a thermal sintering to obtain compact structures. Abstract : Reported here is the fabrication and characterization of a three-dimensional photonic crystal for terahertz frequencies based on 3D printing of Al2 O3 . Specific inks containing Al2 O3, the material required for the structure, are synthesized with the viscosity and rheological properties necessary to be extruded through nozzles of micrometric section. The process is completed by a thermal sintering to obtain compact structures. SEM measurements are performed to evaluate the quality of the structures and measure the geometrical parameters. Finally, the presence of the band gap is demonstrated by THz time-domain spectroscopy.